2000
DOI: 10.1046/j.1524-4725.2000.99278.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A for the Treatment of Axillary Hailey–Hailey Disease

Abstract: Botulinum toxin type A may be an effective and safe nonsurgical alternative for the treatment of benign familial pemphigus in intertriginous areas such as the axillae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 32 publications
(50 reference statements)
1
54
0
1
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31][32][33] Botulinum toxin (axillary or inframammary) may help by reducing sweating, as may breast reduction. [34][35][36] Although ultraviolet light may exacerbate Hailey-Hailey disease, PUVA was apparently effective in some patients. Suberythemal UVB controlled both psoriasis and co-existing Hailey-Hailey disease in another patient.…”
Section: Treatmentmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33] Botulinum toxin (axillary or inframammary) may help by reducing sweating, as may breast reduction. [34][35][36] Although ultraviolet light may exacerbate Hailey-Hailey disease, PUVA was apparently effective in some patients. Suberythemal UVB controlled both psoriasis and co-existing Hailey-Hailey disease in another patient.…”
Section: Treatmentmentioning
confidence: 99%
“…It would also lead to less irritation stimulated by the natural rub in the areas of folds. 12 We presented here two cases in which the BTA proved to be a good adjuvant in patients with recurrent disease and limited response to classical treatment. Its use made it possible to save the use of systemic antibiotics and topic corticosteroids, which was particularly important for a patient that already presented advanced signs of cutaneous atrophy in the fold areas.…”
Section: Discussionmentioning
confidence: 94%
“…For this reason, it is recommended an intensive treatment including those patients with few lesions. 16 Lapiere et al reported the case of a patient who had had an applications of 50U of BTA in each axilla, having had complete remission of the lesions in these areas, 12 similarly to patient 1 who, during the summer, developed lesions on the groin region, site not treated with BTA, while it remained asymptomatic on the axillae.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with axillary Hailey-Hailey disease are treated with botulinum toxin type A showed good response. [16] Other topical modalities are topical antibiotics, topical steroids, tacalcitol another vitamin D3 derivative and cyclosporine. Systemic treatment includes antibiotics, steroids, cyclosporine, dapsone, methotrexate and thalidomide.…”
Section: Figure 3bmentioning
confidence: 99%